A Rare Giant Midesophageal Diverticulum: Fever is the Only Symptom - Qi PX; Zou JN; Zhu J; Huang B; Xi EP; Gao XH (Dove Medical Press, 2021)
Ping-Xin Qi,1,2,* Jia-Ni Zou,3,* Jian Zhu,2 Bin Huang,4 Er-Ping Xi,2 Xu-Hui Gao2 1School of Medicine, Wuhan University of Science and Technology, Wuhan 430065, People’s Republic of China; 2Department of Thoracic Cardiovascular Surgery, General Hospital of Central Theater Command of the People’s Liberation Army, Wuhan 430070, People’s Republic of China; 3Department of Radiology, General Hospital of Central Theater Command of the People’s Liberation Army, Wuhan 430070, People’s Republic of China; 4The First School of Clinical Medicine, Southern Medical University, Guangzhou 510515, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xu-Hui Gao; Er-Ping XiDepartment of Thoracic Cardiovascular Surgery, General Hospital of Central Theater Command of the People’s Liberation Army, 627#, Wuluo Road, Wuchang District, Wuhan, Hubei 430070, People’s Republic of ChinaTel +86-13307195757Fax +86-27-50772388Email whzyygxh@126.com; wo5351@126.comAbstract: A 55-year-old man was treated at the village hospital with six months medical history of recurrent chills and fever. Due to the lack of imaging examination, antipyretic and anti-infective medications were given. Although symptomatic treatment can relieve fever symptoms, symptoms easily flare up again two to three days after taking the drug. Later, the patient suffered from fever again during the COVID-19 epidemic and was sent to our hospital for isolation and treatment. During this hospitalization, chest CT examination is mandatory for all patients in order to meet the requirements of epidemic prevention and control. This led to the inadvertent discovery of a large cystic solid mass in the right thoracic cavity communicating with the esophageal lumen. The patient was preliminarily diagnosed as giant midesophageal diverticulum after three-dimensional CT image reconstruction of the chest was reviewed. Considering the patient’s persistent fever with poor nutritional status, we decided to temporarily place two gastric tubes (diverticulum decompression and gastrointestinal nutrition), and antibiotics were used at the same time as another main treatment. However, after the symptoms eased and nutritional status improved, he refused all further treatment. We believe that this patient’s diverticulum is very classic, and the treatment plan is highly integrated with the needs of epidemic prevention and control and achieves a satisfactory therapeutic effect, so we hope to provide colleagues with new diagnosis and treatment enlightenment through this case.Keywords: giant midesophageal diverticulum, symptom, treatment, imaging